TRAINING-INDUCED CHANGES IN THE TOPOGRAPHY OF MUSCLE TORQUES AND MAXIMAL MUSCLE TORQUES IN BASKETBALL PLAYERS - Krzysztof Buśko (Termedia Publishing House, 2012)
The aim of the study was to detect changes in the maximal muscle torques in male basketball players during a two-year training cycle. We verified the hypothesis that different workloads applied during the preparation and competition periods would result in changes in the maximal muscle torques of the athletes (increase during the former and decrease or no change during the latter period) accompanied by no alteration of the percent muscle topography of all the muscle groups tested. The examinations were conducted on nine senior male basketball players from the Polish national team. Estimations of the muscle torques in static conditions were performed at the end of the preparation (measurements I and III) and competition (measurements II and IV) periods of a two-year training cycle. Eleven muscle groups were studied including flexors and extensors of the trunk and flexors and extensors of the shoulder, the elbow, the hip, the knee, and the ankle. Muscle torques of the shoulder and the elbow insignificantly decreased except for the muscle torque of the flexors of the shoulder. Muscle torques of the flexors and extensors of the trunk as well as of the flexors and extensors of the hip, the knee, and the ankle increased between measurements I and III and between measurements I and IV with the only exception being the muscle torque of the flexors of the knee (which significantly decreased by 7.4%) In the case of the flexors and extensors of the trunk and the flexors and extensors of the hip, the changes appeared to be significant. The sum of the muscle torques of the upper limbs markedly decreased between the preparation (measurement I) and competition (measurement IV) periods. The sum of the muscle torques of the trunk and the lower limbs and the sum of the muscle torques of the eleven muscle groups significantly increased between measurements I and IV. Percent muscle topography significantly decreased for the flexors and extensors of the shoulder and the elbow. Likewise, the muscle topography for the sum of the upper extremities was significantly reduced. No changes in the "flexors-extensors" indices of the shoulder, the elbow, the hip, and the knee were observed during the two-year training cycle.